Medication Administration Errors and Contributing Factors at Nurses Workplace: Literature Review - Sakalauskaitė, Dovilė; Kielė, Viktorija (Slauga. Mokslas ir praktika, 2021)
Abstract. Medication errors are a serious problem that can be a threat to health and patient safety and can lead to mistrust of the health system and the work of professionals. Medication administration errors occur at any stage of patient care and can be related to a variety of influencing factors [1]. This literature review identifies the main medication administration errors, which are grouped into medication administration and incorrect documentation of administered medication groups. Along with medication administration errors, the main reasons why nurses make errors in medication administration are identified. The study focuses on medication administration errors and their determinants in nurses’ work. The aim of the literature review was to analyze medication errors and their determinants in nurses’ work. Methods: an exploratory review was conducted to analyze medication administration errors and their determinants in nurses’ work. The methodology considered five main stages that contributed to a focused analysis of the selected studies. Results of the literature review. It was found that medication errors are influenced by the work environment, which is full of extraneous sounds, other members of the medical team, and conversations unrelated to the administration of medicines. The human factor is also a factor in medication administration errors related to the medication, its dose, or the wrong administration time. Medication administration errors are inevitable, no matter how advanced the patient’s care and nursing techniques.